An Investigation of Pre-Service English Teachers' Proficiency in Basic Teaching Skills During Classroom Practice - Nurlaila Husain; Jolanda Hulda Debora Pilongo; Viranda Palaji (Ideas Publishing, 2023)
English teachers need basic teaching skills. This study examines how seven pre-service English teachers employ the eight core teaching skills. A qualitative study analyzed learning records from teaching practice assessments to explore how pre-service English teachers utilized these skills. It identified eight basic teaching techniques with varying levels of proficiency. First, explanation (93.88%), variation (92.06%), and small group and individual instruction (92.86%). Second, good skills include opening and closing lessons (75.51%), questioning (67.86%), and classroom management (78.57%). Finally, skills reinforcement (61.9%) and leading small group discussions (63.27%) are sufficient. The study indicates some pre-service English teachers need basic skills training.